Diagnosis of fragile X syndrome by using cytogenetic and molecular approach - Tan, Suat Cheng (Universiti Malaysia Sabah, 2007)
The study of fragile X syndrome diagnostic tests was conducted at the Human Genome Center (HGC), Hospital University Science Malaysia (HUSM). In this study, two diagnostic tests were investigated, namely cytogenetic test and molecular test. Cytogenetic test employed standard method of karyotyping to investigate the structural abnormalities of chromosome X. From the karyotypes produced, abnormal fragile site was detected on the chromosome X of one (Sample 6) out of seven samples (14.3%). The presence of fragile site on chromosome X indicates that the patient is afiected by fragile X syndrome. Molecular test was based on the study of the gene that causes this syndrome, namely Fragile X Mental Retardation-I (FMRl) n gene. An extension of CGG triplet repeat region at the 5' end of FMRl gene can cause fragile X syndrome. The focus of molecular test was to investigate the (CGG)n variant in the 7 samples using PCR technique. With the PCR analysis, normal FMRl allele was detected in six out of seven samples (Sample 1 to 7 except Sample 6). The CGG repeats number of these normal samples ranges between 8 and 30 repeats. In Sample 6, no amplified fragment was generated by PCR in the first trial. However, after optimization, a DNA fragment with estimated size 850bp was amplified. The number of CGG repeats of this fragment was 215 repeats. This showed that the particular patient had expanded CGG alleles on FMRI gene and he was diagnosed as fragile X syndrome positive patient. Molecular test diagnostic result was comparable with the diagnostic result of cytogenetic test. Both tests revealed that among the seven samples, only one sample (Sample 6) was fragile X syndrome positive.